2012
DOI: 10.1103/physrevb.85.245404
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo study of small aluminum clusters Aln(n=2–13)

Abstract: Using fixed node diffusion quantum Monte Carlo (FN-DMC) simulations and density functional theory (DFT) within the generalized gradient approximations, we calculate the total energies of the relaxed and unrelaxed neutral, cationic, and anionic aluminum clusters, Al n (n = 1-13). From the obtained total energies, we extract the ionization potential and electron detachment energy and compare with previous theoretical and experimental results. Our results for the electronic properties from both the FN-DMC and DFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…In comparison with the DMC binding energy given in Figure 2, we find that the electron correlation has a very large contribution to the binding energy varying from 58% to 83% of its total value. It also shows that E BE /BE is sensitive to the cluster structure and exhibits an even-odd alternation pattern being similar to those observed in some properties of metal clusters such as the electron binding energy for open and closed shell aluminum clusters [29], indicating that the Li n clusters of even-number size are relatively more favored in terms of correlation energy than the neighbors of odd-number size.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…In comparison with the DMC binding energy given in Figure 2, we find that the electron correlation has a very large contribution to the binding energy varying from 58% to 83% of its total value. It also shows that E BE /BE is sensitive to the cluster structure and exhibits an even-odd alternation pattern being similar to those observed in some properties of metal clusters such as the electron binding energy for open and closed shell aluminum clusters [29], indicating that the Li n clusters of even-number size are relatively more favored in terms of correlation energy than the neighbors of odd-number size.…”
Section: Resultsmentioning
confidence: 65%
“…In this case, our results are in agreement with the CCSD(T) calculations by Wheeler et al [13] and support the monotonic increasing in binding energies per atom observed in Wu's experiments [5] though their binding energies are consistently larger than ours. The correlation energy of a cluster can be obtained by the difference between the DMC and HF energies calculated at a converged basis set [29], E c = E DMC − E HF . Figure 3 shows the correlation energy of the Li n clusters as a function of the cluster size.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a recent quantum Monte Carlo (QMC) study also reported sharp minimum behavior in the vIE of Al n calculations. 53 On the other hand, no DFT functionals used in this study give the minimum value of vIE on Al 7 . All DFT functionals except B3LYP show that the vIE of Al 10 is the minimum for clusters ranging from Al 2 to Al 10 .…”
Section: ■ Computational Detailsmentioning
confidence: 98%
“…DMC is the appropriate tool do deal with systems for which electron correlation plays important role. It can achieve accuracy similar to the best quantum chemistry methods with some advantages like allowing better scaling for medium to large size systems and providing quantum statistical errors . The importance of correlation effects on the energetics and the relative stability of the clusters is investigated.…”
Section: Introductionmentioning
confidence: 99%